2011
DOI: 10.1007/s00436-011-2649-0
|View full text |Cite
|
Sign up to set email alerts
|

Infection patterns of Nile tilapia (Oreochromis niloticus L.) by two helminth species with contrasting life styles

Abstract: The larval stages of Bolbophorus sp. (digenean) and Amirthalingamia macracantha (cestode) are frequently reported in Oreochromis niloticus in Uganda. Little, however, is known about their infection patterns. This study examined the influence of habitat type, host size, and sex and weather patterns on the parasite populations in Uganda. A total of 650 fish were collected between January and November 2008 from a reservoir, cages, fishponds and a stream. The prevalence and intensity of A. macracantha and the prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 49 publications
0
6
1
Order By: Relevance
“…Nonetheless, the correlations of A. macracantha prevalence and mean intensities with T. zillii size (substrate spawner) were weak and contrasted with the study of Akoll et al (2012a), who found positive correlations with O. niloticus size (mouth brooder), probably reflecting host-specific differences. In contrast to our findings, other authors found no relationships between helminth abundance and fish size (Kadlec et al 2003;Ferrari-Hoeinghaus et al 2006;Morenikeji and Adepeju 2009;Madanire-Moyo et al 2010;Ibrahim 2012;Olurin et al 2012).…”
Section: Effects Of Host Size On Parasite Infection Levelscontrasting
confidence: 73%
See 3 more Smart Citations
“…Nonetheless, the correlations of A. macracantha prevalence and mean intensities with T. zillii size (substrate spawner) were weak and contrasted with the study of Akoll et al (2012a), who found positive correlations with O. niloticus size (mouth brooder), probably reflecting host-specific differences. In contrast to our findings, other authors found no relationships between helminth abundance and fish size (Kadlec et al 2003;Ferrari-Hoeinghaus et al 2006;Morenikeji and Adepeju 2009;Madanire-Moyo et al 2010;Ibrahim 2012;Olurin et al 2012).…”
Section: Effects Of Host Size On Parasite Infection Levelscontrasting
confidence: 73%
“…This co-occurrence raises new questions, particularly regarding the parasite`s unknown life cycle. Several authors (Aloo 2002;Florio et al 2009;Akoll et al 2012a;Otachi et al 2014) have reported A. macracantha plerocercoids encysted in the liver or intestinal wall of tilapias. To our knowledge, the only exception was in the original species description (Bray 1974), which did not explicitly mention whether the specimens were found encysted or free in the liver of T. nilotica from Sudan.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Host–parasite interactions may vary in accordance with ecological factors, habitat characteristics and phylogeny (Dobson, 2009; Lafferty, 2009; Akoll et al , 2011). An interesting question in parasitology is why some species or populations are more parasitized than others.…”
Section: Introductionmentioning
confidence: 99%